ANALISIS PENGARUH DANA HIBAH PRESTASI TERHADAP PENDAPATAN ANGGOTA KELOMPOK PENGEMBANGAN PARTISIPASI LAHAN KERING TERPADU - Prayitno, Hendrik (Jurnal Sosial Ekonomi Pertanian, 2007)
The poverty is the massive problem in developing country. One way to solve problem that conducted by government is PIDRA program by matching grant. The aim of this research were (1) to study the average income in society that involvement in PIDRA (participatory integrated development in Rainfed Area) program member either before and after receive the matching grant, (2) to know the social factors that influencing income society, (3) the understand the social stratum by attending the matching grant program. (4) to understand the achievement the PIDRA program in the Lumajang Regency. The location research was conducted in Jambekumbu Village, Senduro Sub District, Lumajang Regency that determined by purposive method. The sample are 30 respondent taken by simple random sampling method. Furthermore the analytical method that used were descriptive, correlation and comparative analysis.The result show that (1) average income among society that before and after receive matching grant is statistically significant different, (2) the social factors that influencing income society are education level (95 confidence level) and the both activity farming namely on-farm and off farm (90 confidence level), (3) there is moving social stratum from poor society category to not poor society category because of PIDRA program, (4) The PIDRA program is quite success. Keywords: PIDRA program, matching grant, income society